Exploring self-reported Sport Mental Health Assessment Tool-1 (SMHAT-1) scores across impairment type of Team USA Paralympic athletes - Galán López, N.; Anderson, T.; Bartley, J. D.; Donaldson, A. T.; Taylor, L.; Adams, W. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Paralympic athletes face additional mental health-related challenges to Olympic athletes due to social forces that differentially affect people with disabilities. Indeed, Paralympic athletes score less favourably (i.e., increased self-reporting of mental health symptoms) than their Olympic counterparts on the Sport Mental Health Assessment Tool - 1 (SMHAT-1). However, the impact of impairment type (IT) and origin of condition (OC; congenital or acquired) on mental health outcomes remains largely unexplored. Therefore, this project examines SMHAT-1 scores considering IT, OC, sex, and competing season among Paralympic athletes. METHODS: Ninety-five Team USA Paralympic athletes competing in Tokyo and Beijing (55 male, 40 female) completed the SMHAT-1, including the components: Athlete Psychological Strain Questionnaire [APSQ], Athlete Sleep Screening Questionnaire [ASSQ; sleep], General Anxiety Disorder [GAD7; anxiety], Patient Health Questionnaire [PHQ9; depression], Alcohol Use Disorders Identification Test-Consumption [AUDIT-C; Alcohol], Cutting, Annoyance, Guilt and Eye openings [CAGE-AID; drug] and Brief Eating Disorders in Athletes [BEDA-Q; food]. Scores on the SMHAT-1 components were treated as binary (i.e., flag or no flag), and continuous variables (i.e., total scores, TS). General linear regression was used to analyse association between TS and IT, adjusting for OC and sex. Risk of flagging by OC, IT, sex, and season (winter/summer) was assessed via *2 tests, with phi (*). RESULTS: For the APSQ, AUDIT-C and BEDA-Q, hypertonia, ataxia and/or athetosis (HAA) showed highest TS among IT (mean+-SE: 23+-2, 3+-1, 14+-2, respectively). Within the PHQ9, GAD7 and ASSQ, the IT short stature showed highest TS (10+-3, 12+-4, 11+-2, respectively). APSQ TS was greater in athletes with HAA (23+-2) compared to impaired muscle power (IMP; 14+-1, p=.049). PHQ9 TS was significantly greater among athletes with HAA (7+-1) compared to IMP (1+-1, p< .001, *=0.37), and were more likely (20%) to flag on the GAD7 (males, 4%; p=.017, OR=0.16). Flagging on the APSQ (*2[1, 96]=45.534, p